(untitled) (Revista Apotheke, 2019)
The present article based on Social Studies of childhood and in the field of Art, derives from the work of conclusion of Pedagogy course of college of Education from the federal university of Rio Grande do Sul (UFRGS), which searched to understand the possibilities involved in ephemeral architecture of game for young children, inspired on contemporary art installations at a early childhood school in Porto Alegre in the first semester of 2018. The methodological journey of investigation was based on research – action. And methodologically was suggested seven sessions of game architectures to a group of children from 2 to 5 years old.Emphasizing the potentiality involved on this assignment, it was possible to identify that the architectures of game were characterized as a space for the symbolic game and to the exercise of childish protagonism.